2011
DOI: 10.1007/s00198-011-1605-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of bone loss in childhood hematologic malignancies: a prospective study

Abstract: This study provides insight into the pathophysiology of bone loss in children receiving cancer therapy and possible interventions to optimize their skeletal health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Duncan et al [9] followed 67 pediatric HSCT patients and found that 37% were deficient at baseline, but in the subgroup of patients !11 years old, 67% were deficient, a figure that accords with our findings (69%). HSCT patients are more prone to develop hypovitaminosis D as a result of sun avoidance, hospitalization, corticosteroid treatment, and diminished intestinal uptake affected by GVHD and bacterial overgrowth [9,[25][26][27]. The lowest baseline levels in our study were found in patients who underwent transplants during winter, spring, and early summerdthat is, before opportunities for sun exposure in northern latitudes become plentiful enough to raise serum levels.…”
Section: Discussionmentioning
confidence: 50%
“…Duncan et al [9] followed 67 pediatric HSCT patients and found that 37% were deficient at baseline, but in the subgroup of patients !11 years old, 67% were deficient, a figure that accords with our findings (69%). HSCT patients are more prone to develop hypovitaminosis D as a result of sun avoidance, hospitalization, corticosteroid treatment, and diminished intestinal uptake affected by GVHD and bacterial overgrowth [9,[25][26][27]. The lowest baseline levels in our study were found in patients who underwent transplants during winter, spring, and early summerdthat is, before opportunities for sun exposure in northern latitudes become plentiful enough to raise serum levels.…”
Section: Discussionmentioning
confidence: 50%
“…Given the good results obtained on this intensive treatment protocol, and now that our diagnostic abilities to test for prognostic translocations, DNA index and MRD have been optimized, we are considering to include a lower intensity arm that would be applicable to patients with lower risk. A study that included 26 patients of our ALL population showed that these patients had lower exercise activity, sun exposure, and bone marker levels than controls [32]. They also had higher parathyroid hormone levels, fat mass, lower bone mass at the spine, hip, and total body, as well as lower increments at these sites on follow-up.…”
Section: Discussionmentioning
confidence: 93%
“…The methods used to analyze vitamin D status were reported in all studies, however only five studies [22,30,32,36,38] reported intra assays' coefficient of variation, which ranged from 3.6 to 14% (Table 1).…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 97%